DAYUN WHISPERS IN BATIK: BUILDING LOCAL CULTURAL IDENTITY THROUGH DAYUN WRITING BATIK - Annisa Aulia Insani; Hambali (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Batik Seni Tulis Dayun is a manifestation of local culture that represents the identity, values, and narrative of the Dayun Village community, Siak Regency. This research aims to examine the production process, the symbolic meaning of the motifs, and the marketing strategy of Batik Seni Tulis Dayun as a form of cultural preservation in the midst of modernization and digitalization. Using an ethnographic approach with participant observation and in-depth interview methods, this research highlights how each stage in the production process from motif printing, pencantingan, coloring, lorod, to finishing has a strong charge of traditional and educational values. The motifs, such as watermelon leaves, pompa angguk, olang-olang dance, and senduduk leaves, were born from the socio-economic reality of the community and reflect their closeness to the natural environment and local culture. In terms of marketing, businesses are utilizing digital platforms and collaboration with the local industry sector to increase exposure and competitiveness. However, challenges such as the digital divide, limited technical training, and lack of regeneration of young batik makers still hamper the development of these businesses. This study emphasizes the importance of cross-sectoral support in maintaining the sustainability of Batik Seni Tulis Dayun as a superior cultural product that can compete in the market while strengthening local identity.